Research on the social integration of the second generation of international Chinese immigrants: Example of children of Chinese immigrants from mainland China aged 17-35 in Lisbon, Portugal - He Yixin (2021)
Portugal has a long history of receiving immigrants, because of the aging of the population, the country's economic activities and pension issues become more and more serious, the role of foreign immigrants in the life of Portuguese society has become increasingly important. Logically that the second generation of immigrants will gradually grow to become an important force in building Portuguese society. However, due to various reasons, such as ethnicity, economic conditions, and social climate, the social status and development of the second generation of immigrants may not be in line with that of the native youth, and there are concerns about the degree of social integration and trends in their social status. This study focuses on the second generation of Chinese immigrants aged 17 to 35 years’ old who are of mainland Chinese origin and currently living in Lisbon, Portugal, with residence status. I will try to explore the identity of the second generation of Chinese immigrants in a multicultural environment by combining the theories of comprehensive cultural identity and social integration with the characteristics of the local Chinese society and integrate data from three aspects: family environment, schooling, and community. The results show that the second generation of immigrants has a strong sense of family mission and responsibility, has a higher level of education than the previous generation, and has a positive correlation between their professional development and the level of social integration of the previous generation.